Analysis of soybean flow in the state of Mato Grosso do Sul: Perspective of the bioceanic corridor (Research, Society and Development, 2021)
The soybean producers in the state of Mato Grosso do Sul (MS) face directly or indirectly the high cost of transport for the flow of the grain by road. Therefore, it is necessary to find alternatives to increase the efficiency of this flow, thus increasing the profitability of producers. This study evaluates the use of the Mercosur-Chile bioceanic corridor in comparison with the main routes for soybean distribution from MS to the Asian market - the main importing market. To this end, the multi-criteria Analytic Hierarchy Process (AHP) methodology was adopted, which aims to evaluate alternatives based on criteria and sub-criteria. The primary data was collected via questionnaires applied to professionals in the area: commercialization, logistics, and agricultural consultants. Through this, the following criteria were determined: infrastructure, cost, environmental impact and time; secondary data were acquired in several scientific databases: Scopus, Science Direct to measure the weights of the criteria and sub-criteria: roads, ports, sea freight, road freight, tolls, port tariffs, CO2 emission, fuel consumption, travel time, road distance and sea distance. The results indicated that the best route for the flow of soy production in Mato Grosso do Sul to the Asian market continues to be through the port of Santos, thus suggesting the need for new strategic studies for the use of the bioceanic corridor in the state.